Peran Guru Pai Dalam Pembentukan Karakter Siswa Di Mts Darul Ma’rifah Rangkasbitung - Agung Jaenudin (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2024)
This study aims to review in depth the role of PAI Teachers in the formation of character education of students of Madrasah Tsanawaiyah (MTs) Darul Ma'rifah Rangkasbitung. Character education is an important aspect in the holistic development of students, and PAI Teachers have a strategic position in integrating moral and ethical values in the learning process. The research method used is a qualitative approach with data collection techniques through the collection of various reading sources, journals, books and other documents that support the topic of discussion. In addition, the author also made direct observations to the research location to obtain the required data. The results showed that there were roles of PAI Teachers in the formation of character education of MTs Darul Ma'rifah Rangkasbitung students, including their roles as: modeling, supervision, coaching, and punisher. With this role, it is expected to maximize the formation of character education in MTs Darul Ma'rifah Rangksibutn students and become an additional reference material for readers who want to analyze the role of PAI Teachers further.